Technology Of Black Cincau Liang Tea As Diversified Products In Black Cincau Gel Producer At Batu City - Tri Dewanti Widyaningsih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
ABSTRACT Black cincau (Mesona palustris BL) or black grass jelly is traditional beverage ingredient that is believed has efficacious for health, but the black cincau gel in the market known asunhygienic food and has shortshelf life. Liang tea of black cincau is a kind of processed product development of black cincau. Liang tea or herbal tea made from of black cincau extracts with the addition of other herbs such as ginger, cinnamon or pandan leaves.